2023
DOI: 10.3390/diseases11040136
|View full text |Cite
|
Sign up to set email alerts
|

Increased Salivary IL-1 Beta Level Is Associated with Poor Sleep Quality in University Students

María Luisa Ballestar-Tarín,
Vanessa Ibáñez-del Valle,
Mayra Alejandra Mafla-España
et al.

Abstract: Poor sleep quality is a major public health concern for all ages. In particular, university students often face stress levels and changes in social life habits that negatively influence their quality of sleep. This could be associated with psychological well-being in terms of anxiety and depressive symptoms, stress levels, and a poor self-perceived health status. The increases in the pro-inflammatory cytokine interleukin 6 (IL-6), IL-1 beta (IL-1β), and tumor necrosis factor alpha (TNFα), in blood have been li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(82 reference statements)
0
2
1
Order By: Relevance
“…The results of increased BDNF contrast with previous reports that measured BDNF in serum or plasma samples, which found lower concentrations of the neurotrophic factor in the most severely depressed patients [51]. In addition, effective treatments for depression (antidepressant drugs or other non-pharmacological interventions) are able to increase BDNF levels [22][23][24][25][26][27][28]56].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The results of increased BDNF contrast with previous reports that measured BDNF in serum or plasma samples, which found lower concentrations of the neurotrophic factor in the most severely depressed patients [51]. In addition, effective treatments for depression (antidepressant drugs or other non-pharmacological interventions) are able to increase BDNF levels [22][23][24][25][26][27][28]56].…”
Section: Discussioncontrasting
confidence: 93%
“…Montón et al [50] validated the Goldberg scale in the Spanish population in a sample of 444 patients aged 19 and over. The Goldberg scale has previously been used to assess anxiety and depression symptoms among college students [51,52], healthcare professionals [53], and the Spanish general population [54].…”
Section: Depressive and Anxiety Symptomsmentioning
confidence: 99%
“…Poor sleep quality can have an impact on individuals of all ages and populations [1], and particularly health science students, whose academic careers are highly stressful [2]. A recently published umbrella review reported a prevalence of self-reported sleep problems in medical and nursing students between 40 and 55% [3][4][5][6][7][8]. The prevalence of sleep problems among medical students varies across countries; for example, in China, the prevalence seems to be as low as 25% [9,10], while Iran had the highest prevalence of around 58% [11].…”
Section: Introductionmentioning
confidence: 99%